2019
DOI: 10.1111/1745-9125.12223
|View full text |Cite
|
Sign up to set email alerts
|

Testing a rational choice model of “desistance:” Decomposing changing expectations and changing utilities

Abstract: We argue that a rational choice framework can be used to explain declines in offending from adolescence to young adulthood in two ways. First, subjective expectations of offending can be age graded such that perceptions of rewards decrease and perceptions of risks and costs increase. Second, the marginal (dis)utility of crime may be age graded (e.g., preferences for risks, costs, and rewards). We examine changes in offending from adolescence to young adulthood among a subset of individuals from the Pathways to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 99 publications
2
20
0
Order By: Relevance
“…Adolescents are more affected by peers in their risky decision‐making than are children or adults (Berndt, ; Blakemore & Mills, ; Gardner & Steinberg, ; Steinberg & Monahan, ). Researchers have shown that this age patterning in susceptibility to peer influence can be explained by heightened sensation seeking (i.e., risk preference; Steinberg et al., ), social reward‐sensitivity (i.e., social preference; Chein et al., ; Thomas & Vogel, ), and reliance on the “hot” affective system (i.e., time preference; Casey, Jones, & Hare, ; Cauffman et al., ) during adolescence, combined with immature capacities for self‐control (Steinberg et al., ). There is even an indication of within‐individual change in the type of social preferences, in that adolescents prioritize popularity goals over other social goals such as friendship and romantic involvement (LaFontana & Cillessen, ).…”
Section: Integrative Perspectives On Peers and Decision‐makingmentioning
confidence: 99%
“…Adolescents are more affected by peers in their risky decision‐making than are children or adults (Berndt, ; Blakemore & Mills, ; Gardner & Steinberg, ; Steinberg & Monahan, ). Researchers have shown that this age patterning in susceptibility to peer influence can be explained by heightened sensation seeking (i.e., risk preference; Steinberg et al., ), social reward‐sensitivity (i.e., social preference; Chein et al., ; Thomas & Vogel, ), and reliance on the “hot” affective system (i.e., time preference; Casey, Jones, & Hare, ; Cauffman et al., ) during adolescence, combined with immature capacities for self‐control (Steinberg et al., ). There is even an indication of within‐individual change in the type of social preferences, in that adolescents prioritize popularity goals over other social goals such as friendship and romantic involvement (LaFontana & Cillessen, ).…”
Section: Integrative Perspectives On Peers and Decision‐makingmentioning
confidence: 99%
“…Criminal law norms, determining which socially dangerous acts are criminal, and establishing the types and amounts of punishments for their commission, thereby have a preventive effect on society as a whole. This effect is that citizens have a clear idea of certain actions as criminal, with the association in their minds of criminal punishment as an inevitable consequence of the crime (Thomas & Vogel, 2019;Thomas et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Overwhelmingly, research has focused on the process of desistance as occurring in adulthood (Craig et al, 2014; Giordano et al, 2002; Laub & Sampson, 2003; Thomas & Vogel, 2019). This focus reflects the established age-crime curve, where offending behavior increases through adolescence before declining substantially as one enters adulthood (Piquero et al, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rational choice has been further operationalized within desistance research by considering social and personal rewards of criminal behavior against perceived risk of arrest using data from the Pathways to Desistance study. Perceived social costs of crime reduce offending behavior in adulthood, but not adolescence, while the social rewards of misbehavior significantly influence adolescent offending, but not young adult criminal behavior (Thomas & Vogel, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation